2012
DOI: 10.1590/s1806-83242012000600009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fluoride-containing adhesives and bleaching agents on enamel bond strength

Abstract: This study evaluated the influence of fluoride-containing carbamide peroxide (CP) bleaching agents and adhesive systems on bonded enamel interfaces that are part of the dynamic pH cycling and thermal cycling models. The buccal surfaces of 60 bovine incisors were restored with a composite resin and bonded with three-and two-step, etch-and-rinse, fluoride-containing adhesives, Optibond FL (FL) and Optibond Solo Plus (SP), respectively. Restored teeth were subjected to thermal cycling to age the interface. Both S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
10
0
4
Order By: Relevance
“…The very short time of ozone gas application when compared with the application time of other oxidants, like bleaching agents, could be another explanation for the lack of ozone effect on SBS values in the present study 7,8 .…”
Section: Discussionmentioning
confidence: 60%
“…The very short time of ozone gas application when compared with the application time of other oxidants, like bleaching agents, could be another explanation for the lack of ozone effect on SBS values in the present study 7,8 .…”
Section: Discussionmentioning
confidence: 60%
“…57 Leonetti ve arkadaşları, mineye 21 gün süreyle uygulanan %16 karbamid peroksitin, Single Bond 2'nin dentine bağlanma dayanım değerlerini bir miktar düşürdüğünü ancak bunun anlamlılık sergilemediğini bildirmişlerdir. 58 Cavalli ve arkadaşları, 59 beyazlatma ajanlarının fluor içeren adezivlerin (Optibond FL, Optibond Solo Plus) mineye olan bağlanma dayanım değerleri üzerin-deki etkisini incelemişlerdir. Araştırmacılar, %10'luk karbamid peroksitin, her iki bağlayıcınında mineye olan bağlanma dayanım değerlerini anlamlı olarak düşürdüğünü ileri sürmüşlerdir.…”
Section: Beyazlatma Işlemiunclassified
“…3 However, the bond strength of resinous materials to the teeth is temporarily reduced following bleaching, 3,[5][6][7] which might be associated with bond failure and the risk of micro-infiltrations, which threaten the longevity of restorations.…”
Section: 5005/jp-journals-10024-1672mentioning
confidence: 99%
“…7 Nevertheless, Cavalli et al 7 observed that the bond strength of restorations decreased after whitening treatment, even when fluorine was added to the bleaching agent. Therefore, further studies are needed to elucidate the influence of the addition of potassium nitrate, sodium, and calcium fluoride on the bond strength of resinous materials to the tooth structure.…”
mentioning
confidence: 99%